The Patriot War of 1837-1838: Locofocoism With a Gun? - Bonthius, Andrew (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract This paper presents a reinterpretation of the causes for the US Patriot movement of 1837-38, which rose up in support of the Canadian rebellion in Upper Canada (UC) initiated by William Lyon Mackenzie (the companion rebellion in Lower Canada is not considered in this paper since its causation was arguably considerably different). Most traditional treatments of this event, by US historians in particular, are stuck in narrative mode and lack convincing interpretation and analysis. The US Patriot war is usually quickly dismissed as the work of a few Anglophobes and adventurers seeking land and coin. The hypothesis advanced here suggests that the US Patriot movement and its progenitor rebellion in UC may be seen as an expression of the social class tensions growing out of the transition from a subsistence-barter/ household economy and culture to the more impersonal commodity market economy —a transition that was proceeding in an uneven and combined manner on both sides of the nominal Canada/us border. Mackenzie's UC rebellion was both motivated by and encouragement to radical Democratic anti-bank forces in the US. Historians are urged to consider the Patriot movement in the larger context of class conflict and accommodation then being played out on a shared Canadian/American stage.